Status of the CLIC phase and amplitude stabilisation concept - Schulte, D; Andersson, A; Bettoni, S; Corsini, R; Dubrowskiy, A; Gerbershagen, A; Jeanneret, J; Morpurgo, G; Sterbini, G; Stulle, F; Tomas, R; Marcellini, F; et al. (2011)
In CLIC very tight tolerances exist for the phase and amplitude stability of the main and drive beam. In this paper we present the status of the CLIC beam phase and amplitude stabilisation concept. We specify the resulting tolerances for the beam and technical equipment and compare to measurements.